mSphere of Influence: Discovering New Layers of Complexity in the Immune System - Drummond, Rebecca A. (mSphere, 2021)
Rebecca Drummond works in the field of antifungal immunity. In this mSphere of Influence article, she reflects on how papers by Amit et al. (H. Keren-Shaul, A. Spinrad, A. Weiner, O. Matcovitch-Natan, et al., Cell 169:1276–1290, 2017) and Ayres et al. (K. K. Sanchez, G. Y. Chen, A. M. P. Schieber, S. E. Redford, et al., Cell 175:146–158, 2018) made an impact on her by introducing her to new concepts in immune system complexity.